EFEKTIFITAS PROSEDUR KEPABEANAN TERKAIT DENGAN DWELLING TIME UNTUK IMPORTASI DI KANTOR PELAYANAN UTAMA BEA DAN CUKAI TIPE C SOEKARNO HATTA TAHUN 2017 - Tony Triyulianto; Pebriana Arimbhi; Emanuel Ageng Pratama Labupili (Jurnal Pajak Vokasi (JUPASI), 2019)
This research is intended to discuss the effectiveness of customs procedures related with dwelling time for importation in the Main Service Office of Customs and Excise Type C Soekarno Hatta in 2017. The main problem in this research is how the level of effectiveness of customs procedures and its relation with dwelling time for importation process in KPUBC Type C Soekarno Hatta. With ineffective implementation of customs procedures in the process of imported goods resulted in high dwelling time figures. With the existence of high dwelling time will certainly inhibit the smooth flow of importation process and the release of imported goods.This research is a qualitative descriptive research with data collection techniques in the form of interviews and secondary data. The results of interviews and data are then processed and analyzed to determine the effectiveness of customs procedures related to dwelling time for the importation in KPUBC Type C Soekarno Hatta in 2017.The results of this research, the authors conclude that KPUBC Type C Soekarno Hatta in 2017 seen from the aspect of the plan or program and the rules and regulations included in the category effective, whereas from the duties or functions and objectives or ideal conditions included in the category less effective. Therefore, for the future KPUBC Type C Soekarno Hatta can improve the effectiveness of customs procedures by minimizing the constraining entities that occur by using appropriate entrepreneurs. The author also advises KPUBC Type C Soekarno Hatta to provide performance guidance training to be more effective, to customs service users to learn all the rules and latest information on customs procedures and for DJBC itself is expected to take an active role in it.